(untitled) - Kronenburger, John (Clifton Park, NY, 2008)
Analog & Digital Signal Processing: A Computational Approach provides a thorough yet mathematically accessible introduction to signal processing. With the increasing presence of digital signal processing (DSP) in everyday life, in the form of devices such as CD and DVD players, digital cameras, wireless telephones, and voice recognition, it has accordingly become a central element in the design of a variety of systems and applications. This book responds to this trend by presenting readers with a strong foundation of fundamental DSP concepts and designs. Unlike traditional DSP books, a computational approach is used to help readers spend less time deciphering mathematical complexities and more time implementing practical DSP techniques. MATLAB, an industry favorite scientific software package, is used to conduct the computations of the concepts discussed. With coverage of introductory concepts such as sampling, frequency analysis, transfer functions, and filter design, as well as advanced topics like statistical signal processing, adaptive filters, image processing, and wavelet analysis, this is an ideal resource for readers of all levels who are seeking a comprehensive understanding of relevant DSP concepts for today's industry professionals.
Keywords: Signal processing,Linear integrated circuits.,Signal processing,Thiết lập tín hiệu; Digital techniques,Digital techniques,Mathematics.,Kỹ thuật số